Association Between Abdominal Aortic Atherosclerosis and Carotid Artery Atherosclerosis. Issue 4 (October 2013) - Haygert, Carlos Jesus P; Alves, Giordano RT; Suzigan, Bruna H; Souza, Lucas V de; Naujorks, Alexandre; Barbisan, Juarez
No abstract available